Redescription of the holotype of Bostrichoclerus bicornus Van Dyke, 1938, a rare species of the New World Tillinae Fauna (Coleoptera: Cleridae), with some taxonomic notes - Burke, Alan F.; Leavengood, John M. Jr.; Scholtz, Clarke H.; Sole, Catherine L. (Zootaxa, 2019)
Bostrichoclerus bicornus Van Dyke is known from southwest United States and northwest Mexico. To date, only two specimens have been captured: the holotype, collected on Isla Angel de la Guarda, in the Gulf of California, Mexico, and a second individual collected in San Bernardino County, California, United States. The original description of B. bicornus is brief and lacks any images. Considering its rarity, we present the redescription of this species based on the examination of the holotype and compare this taxon to similar genera of New World Tillinae. Images of the holotype and the Bostrichoclerus specimen collected in southern California are given. We conclude that B. bicornus is undoubtedly a member of the subfamily Tillinae with unclear intergeneric relations in the group.